FINANCIAL PERFORMANCE SEGMENTATION CHANGES ON PROPERTIES AND REAL ESTATE INDUSTRIES FOR ACQUISITION - Dwi Wuryantadi; Jerry Heikal (Cerdika: Jurnal Ilmiah Indonesia, 2023)
Mergers and acquisitions of companies are generally understood as efforts to develop a company for the better, by combining strengths and/or compensating for weaknesses in one company with strengths in other companies. One of the processes that must be carried out is to find a public company that is feasible to be acquired, according to the problem formulation. How do you determine which prospective companies in the property and real estate industry are eligible for acquisition? Data from 34 issuers were analyzed based on several financial ratios, namely Sales, D/E Ratio, ROA, ROE and NPM and segmented changes in their financial performance into five clusters using the IBM SPSS version 26 application by carrying out K-Mean Cluster Classification, the results of the analysis show. Of the 14 issuers, there were 2 issuers whose sales performance and financial performance deteriorated, namely: LPKR (Lippo Karawaci Tbk) and SMRA (Sumarecon Agung Tbk). There are 12 Issuers that have experienced an increase in Sales Performance and Financial Performance. There is one issuer that has experienced an increase in Sales and Financial Performance of 1 point in a very good cluster position at this time that is eligible to be made an acquirer company, namely BSDE (Bumi Serpong Damai Tbk).